Functional Status, Supportive Care Needs, and Health-Related Quality of Life in Advanced Lung Cancer Patients Aged 50 and Older - Zhe-Peng Huang; Hui-Lin Cheng; Soon Yue Loh; Karis Kin Fong Cheng (Elsevier, 2020)
Objective: This study aimed to examine the levels of functional status, supportive care needs, and health-related quality of life (HRQOL), and their relationships reported by advanced lung cancer patients aged 50 and older. Methods: A cross-sectional descriptive correlational study was conducted with 103 participants recruited from a cancer center in Singapore. Functional status, supportive care needs, and HRQOL were measured using validated instruments. Descriptive statistics were used to describe the sample profiles. Univariate and multivariate regression analyses were adopted to determine factors that were associated with HRQOL. Results: About 70.9% of participants were dependent in at least one instrumental activities of daily living (IADL). The mean number of unmet needs rated by participants was 9 (range = 0-28). The top three ranked items with moderate-to-severe unmet needs were "not being able to do things you used to do" (28.2%), "fear about cancer spreading" (25.3%), and "lack of energy/tiredness" (25.2%). Higher IADL scores were significantly associated with better HRQOL, whereas higher levels of supportive care needs, particularly in psychological domain significantly predicted poorer HRQOL in most domains. Conclusions: This study found that poor functional status and unmet supportive care needs are common in advanced lung cancer patients. Psychological needs and functional status are associated with patients' HRQOL. Future interventions incorporating functional assistance and psychological support may increase HRQOL in this population.